Comparison of Directigen FLU-A with viral isolation and direct immunofluorescence for the rapid detection and identification of influenza A virus. - Waner, J L (1991)
Directigen FLU-A, an enzyme immunoassay membrane test, was compared prospectively to isolation in cell culture and direct immunofluorescence (IF) for the detection of influenza A virus. One hundred ninety specimens were evaluated by Directigen FLU-A and cell culture; 184 of these specimens were also tested by direct IF. The sensitivity of Directigen FLU-A compared to isolation in cell culture and direct IF was 100%. The specificities of Directigen FLU-A compared to isolation and direct IF were identical, 91.6%. Fourteen specimens that were positive by Directigen FLU-A did not yield virus in culture; two of the specimens, however, were positive by direct IF, and four other specimens were not specimens of choice for the test. A positive Directigen result had positive predictive values of 62.6 and 75.0% compared to isolation and direct IF, respectively; a positive Directigen result with an intensity reading of 2+ or greater, however, had positive predictive values of 85 and 100% compared to isolation and direct IF, respectively. In all comparisons, the negative predictive value was 100%. There was no evidence that cross-reactivity occurred with non-influenza A antigens. Directigen FLU-A should serve as a convenient screening test for influenza A and as a rapid test supported by isolation in cell culture during an influenza outbreak.